URGENSI MORAL DALAM DISKURSUS AL-QUR’AN DAN HADITH - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (IAINU Kebumen Prodi IAT, 2023)
The paper discusses the foundational role of al-Quran and Prophetic narrations (al-hadith) in Islamic intellectual history and its moral-legal tradition. It looks into the impact of its discursive religious-spiritual ideal and teaching and its historical significance in developing and fulfilling its fundamental role and social obligation in delivering and justifying the principle of morality and fairness, contributing to medieval civilization and the formation of higher ethical-legal framework, and its state-of-the-art manifestation as set forth in the tafsir of Risalah al-Nur by Said Nursi. The study is based on library research using historical and qualitative approaches and documentation technique. The finding shows that the position of al-Quran and hadith was vital in informing and shaping the historical concept and understanding and paradigm of tawhid and in reinforcing the religious belief and practice and spiritual consciousness of the ummah. In the context of modern commentary, its philosophical ideas and interpretation were brought forth by Said Nursi in Risalah al-Nur that contextualize its discursive history and outline its religious and scientific significance and transcendental values and its role in the current debates of the philosophy of science, revelation, and scripture.